2015
DOI: 10.1007/s00726-015-2050-x
|View full text |Cite
|
Sign up to set email alerts
|

Incremental effects of 28 days of beta-alanine supplementation on high-intensity cycling performance and blood lactate in masters female cyclists

Abstract: Within the aging population, there exists a subset of individuals termed masters athletes (MA). As masters-level competition increases in popularity, MA must find methods to enhance individual athletic performance. Longitudinal beta-alanine (BA) supplementation is suggested to enhance physical capability during exercise; however, these effects have not been evaluated in MA. To examine the longitudinal effects of BA on time to exhaustion (TTE), total work completed (TWC), and lactate clearance in female MA cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 38 publications
2
44
0
1
Order By: Relevance
“…However, the study of Brisola et al [ 8 ] with water polo players showed that 4 weeks of β-alanine supplementation slightly improved repeated sprint ability in specific-protocol testing. Furthermore, some studies also did not find significant changes in after supplementation with β-alanine [ 19 , 23 , 42 ], indicating that β-alanine supplementation may have little or no influence on this physiological variable. In addition, the only study [ 27 ] in the literature that found a significant reduction in with β-alanine supplementation did not use pure β-alanine and the authors considered the reduction as an unexpected effect.…”
Section: Discussionmentioning
confidence: 99%
“…However, the study of Brisola et al [ 8 ] with water polo players showed that 4 weeks of β-alanine supplementation slightly improved repeated sprint ability in specific-protocol testing. Furthermore, some studies also did not find significant changes in after supplementation with β-alanine [ 19 , 23 , 42 ], indicating that β-alanine supplementation may have little or no influence on this physiological variable. In addition, the only study [ 27 ] in the literature that found a significant reduction in with β-alanine supplementation did not use pure β-alanine and the authors considered the reduction as an unexpected effect.…”
Section: Discussionmentioning
confidence: 99%
“…Where data were incomplete, authors were contacted to obtain the relevant information. Data from one study were not received,23 meaning that this study was not included in the analyses.…”
Section: Methodsmentioning
confidence: 99%
“…As β-alanine is considered primarily effective within 1-to 10-minute time frames [9], endurance athletes who undertake interval training sessions within that duration may benefit from an improved adaptive response to training by accumulating a greater workload during each session. This may be due to a number of inter-related factors including improved pH buffering [43], which can allow a greater reliance on aerobic metabolism and thus reduced accumulation of glycolytic metabolites for the same exercise intensity [44], decreased levels of blood lactate during the recovery from supra-maximal exercise [45], a reduction in oxidative stress due to the antioxidant effects of carnosine that could allow improved recovery between demanding workouts [46][47][48], an increased threshold for neuromuscular fatigue [41], and/or reduced feelings of fatigue during periods of heavy training [42,44]. It has also been suggested that increases in calcium sensitivity [49], or in calcium re-uptake [50], may also play a role in the ergogenic effects of β-alanine by helping to slow the decline in muscle performance during fatiguing exercise.…”
Section: Beta-alaninementioning
confidence: 99%